(untitled) (Research, Society and Development, 2020)
This article aimed to describe the main contributions of a continuing education course, structured to establish a space for dialogue and construction of knowledge on the theme of Inclusive Education. For this, the Problem Based Learning methodology was used, with conceptual maps as a proposal for learning evaluation, and a Likert attitudinal scale to evaluate the course. 24 coordinators of basic education of a city in the interior of Goiás participated in the proposal. The data, obtained from the paired evaluation of the maps before and after the course, were compared by the Wilcoxon marked posts test for paired samples. The results revealed statistically significant growth in the number of new concepts related to school inclusion in the post-course maps than in the pre-course (p<0.01). By the analysis of the attitudinal questionnaire, it was possible to verify that 100% of the participants considered the course motivating, useful and would recommend it to others. Thus, trough the observation of the mediator, and also the analysis of the conceptual maps and the data obtained through the attitudinal questionnaire, it is possible to infer that there was an addition of key concepts related to the inclusive education, that the course was useful to promote reflection in the intended context, and that the course proved to be an important tool in stimulating the study and updating of themes related to the inclusion of students with special educational needs.